Hubungan Kontrol Diri dan Spiritualitas dengan Kenakalan Remaja di Kota Padang - Randy Refnandes; Lili Fajria; Nelwati Nelwati (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The number of juvenile delinquency continues to increase, it can be seen from the high number of brawls, drugs and illegal racing carried out by teenagers. Some of the influencing factors are self-control and spirituality. This study aims to determine whether there is a relationship between self-control and spirituality with juvenile delinquency. The research design used a cross sectional study method with a sample of 175 teenagers at Di Kota Padang, using a stratified random sampling technique. This research was conducted in January - July 2022. The measuring instruments used were self-control questionnaires, DSES (Daily Spiritual Experience Scale) and juvenile delinquency. Data processing was carried out using the chi-square method. The results of this study indicate that most (54.9%) of respondents have a good spirituality level and most (65.7%) of respondents have less self-control and most (58.3%) of respondents commit juvenile delinquency, there is a significant relationship between self-control and juvenile delinquency (p-value = 0,037) and a significant relationship between spirituality and juvenile delinquency (p-value = 0,022). The results of this study expect the school to hold extracurricular activities that generate interest for teenagers both in the field of sports and religion which is balanced by completing adequate facilities and infrastructure so that teenagers avoid the bad effects of juvenile delinquency.